The influence of microalgae on vegetable production and nutrient removal in greenhouse hydroponics. (10th January 2020) - Huo, Shuhao; Liu, Junzhi; Addy, Min; Chen, Paul; Necas, David; Cheng, Pengfei; Li, Kun; Chai, Hope; Liu, Yuhuan; Ruan, Roger
Abstract: The effect of microalgae on plant growth and nutrient removal was assessed for three vegetables (arugula, purple kohlrabi and lettuce) grown entirely using nitrate-rich synthetic wastewater in greenhouse hydroponics. Results showed that the response of the vegetables to microalgae varied. Microalgae had a negative effect on arugula growth, but in the purple kohlrabi and lettuce groups, there were no negative effects or even an increase in vegetable production. The dissolved oxygen (DO) and microalgae biomass concentrations in the group with microalgae added were relatively higher. pH increased because of microalgae photosynthesis and decreased due to NH3 –N removal processes. The presence of microalgae, especially Chlorella vulgaris addition, can significantly improve the removal rate of total dissolved solids, total nitrogen (TN), and total phosphorus (TP), but not COD. The contribution of each vegetable and microalgal consortia on the N or P removal in greenhouse hydroponics was different. The P removal efficiency were satisfactory in all groups, especially in the natural microalgae treatment where P removal rate reached more than 98%. In some cases, vegetable hydroponics could be upgraded with microalgae co-cultivation which could be an ecofriendly and economically sustainable production system. Graphical abstract: In the three conditions: Natural microalgae, Microalgae added, and Microalgae-free, the effects of microalgae on vegetable growth and nutrient removal were revealed in greenhouse hydroponics. Image 1 Highlights: Influences of microalgae on vegetable productivity in hydroponics was varied. pH showed changes due to microalgae photosynthesis and N removal processes. Dissolved oxygen and microalgal biomass were higher in microalgae added group. Microalgae can significantly improve total dissolved solids, N and P removal rate.